Notice of Retraction: Experimental simulation analysis for single phase transformer tests - Ali N. Hamoodi; Bashar A. Hammad; Fawaz S. Abdullah (Bulletin of Electrical Engineering and Informatics, 2020)
Notice of Retraction-----------------------------------------------------------------------This article has been retracted by the publisher.After careful and considered review of the content of this paper by a duly constituted expert committee, this paper has been found to be in violation of IAES's Publication Principles.We hereby retract the content of this paper. Reasonable effort should be made to remove all past references to this paper.The presenting author of this paper has the option to appeal this decision by contacting info@iaesjournal.com.-----------------------------------------------------------------------Transformer is one of main components in electrical power system which role to increase or reduce voltage. Characteristics of transformer would be vital to ensure the voltage is fully transferred. A single-phase transformer is a type of power transformer that utilizes single-phase alternating current, meaning the transformer relies on a voltage cycle that operates in a unified time  phase. This article describes a workflow executed with Mat lab simulation and practical measurements for single-phase power transformer, no-load, short-circuit test and load test are achieved in this work. The test procedures are implemented on areal transformer (terco-type) which has a specification (1 KVA, 220/110 V, 50 Hz). Finally, the simulation results are appeared a proximately seminar from the practical results. The results indicated that the the technique and manner which presented in the current study can be depended as a miniproject in electrical technology mater for undergraduate studies.